Analysis of Brand Perception and Relevance of Sukarara Woven Fabric Motifs in the Context of Cultural Identity and Market - Kembang, Lale Puspita; Dewi Rispawati; Maryanti, Sri (Universitas Nahdlatul Ulama Sidoarjo, 2024)
This study aims to analyze the level of Brand Awareness of Sukarara woven fabric motifs among domestic tourists. The method used in this study is a quantitative survey with data collection through questionnaires distributed to tourists visiting the area. The research sample consisted of 120 respondents selected through non-probability sampling techniques. The results of the study indicate that the level of Brand Awareness of Sukarara woven fabric motifs is at the brand recall level which is included in the high category, with an average value of 2.89 which is on a scale of 2.52 - 3.27. This finding indicates that domestic tourists have recognized and remembered Sukarara woven fabric motifs, although the product has not been the main choice when buying woven fabrics. This study provides important insights for craftsmen and marketers to formulate more effective marketing strategies to increase the attractiveness and relevance of Sukarara woven fabrics in the market so that they can transform from being simply recognized to being the main choice among consumers. Thus, this study is expected to contribute to the development of the local weaving industry and cultural preservation through increased brand awareness.